Treatment approaches and outcome trajectories for youth with high‐risk opioid use: A narrative review. Issue 3 (29th April 2021) - Westenberg, Jean Nicolas; Tai, Andy M. Y.; Elsner, Julie; Kamel, Mostafa M.; Wong, James S. H.; Azar, Pouya; Vo, Dzung X.; Moore, Eva; Mathew, Nickie; Seethapathy, Vijay; Choi, Fiona; Vogel, Marc; et al.
Abstract: Aim: First use of opioids often happens in adolescence and an increasing number of opioid overdoses are being reported among youth. The purpose of this narrative review was to present the treatment approaches for youth with high‐risk opioid use, determine whether the literature supports the use of opioid agonist treatment among youth and identify evidence for better treatment outcomes in the younger population. Methods: A search of the literature on PubMed using MeSH terms specific to youth, opioid use and treatment approaches generated 1436 references. Following a screening process, 137 papers were found to be relevant to the treatment of high‐risk opioid use among youth. After full‐text review, 19 eligible studies were included: four randomized controlled trials, nine observational studies and six reviews. Results: Research for the different treatment options among youth is limited. The available evidence shows better outcomes in terms of retention in care and cost‐effectiveness for opioid agonist treatment than abstinence‐based comparisons. Integrating psychosocial interventions into the continuum of care for youth can be an effective way of addressing comorbid psychiatric conditions and emotional drivers of substance use, leading to improved treatment trajectories. Conclusions: From the limited findings, there is no evidence to deny youth with high‐risk opioid use the same treatment options available to adults. A combination of pharmacological and youth‐specific psychosocial interventions is required to maximize retention and survival. There is an urgent need for more research to inform clinical strategies toward appropriate treatment goals for such vulnerable individuals.